Stimulus-Organism-Response (S-O-R) Theory Approach on Loyalty and Hospital Switching Model - Herni Justiana Astuti; Nor’ain Abdullah; Wiwin Dyah Priwanti; Suryo Luqman Hakim (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study aims to investigate how patient loyalty and hospital switching are impacted by service quality and hospital image via satisfaction.Methodology: Purposive sampling is used in this approach, where the prerequisite is a patient who have undergone treatment at least 3 times in the last 3 months and have used other hospital care. Based on this technique, a sample of 100 patients. Data were analyzed using structural equation modeling using partial least square technique, via two distinct but sequentially related phases.Finding: The findings demonstrate that satisfaction is positively and significantly impacted by hospital image and service quality.  Only loyalty is impacted by the hospital's reputation; transferring hospitals is not directly impacted.  However, hospital switching and loyalty are unaffected by service quality. Patient satisfaction can only mediate the relationship between the hospital image and hospital switching as well as patient loyalty, which does not apply to service quality. This study indicates that patient stimulus comes from external influences, where service quality and hospital image provide individual impacts (Organism) reflected in feelings of satisfaction or dissatisfaction. This then leads to a response, which is loyal patients. The satisfaction or dissatisfaction felt by patient as ‘Organism’ does not affect their decision to switch services to another hospital.Conclusion: Patient loyalty and satisfaction are directly impacted by hospital image.  Patient satisfaction is directly impacted by service quality, but loyalty is not much impacted.  Only patient satisfaction can operate as a mediator in the interaction between loyalty and hospital image.